Chapter Il viaggio come paradigma esistenziale nella Bibbia e nella letteratura ebraica antica - Zatelli, Ida (Studi e saggi, 2021)
The divine command issued to Abraham in Genesis 12,1: «Go (lek-lekà) from your country and your kindred and your father's house to the land that I will show you», presents us with a dramatic image of the human existence as it unfolds in the Bible and in the ancient Hebrew texts. It is a departure for an undisclosed destination from which there is no coming back, an act of unconditional trust. The patriarchs describe themselves as wanderers and nomads (see Genesis 47,9) and the road (derek), the way becomes a metaphor for life. True life lies beyond the known world; only those who take upon themselves to embark on a long and perilous journey will see the "promised land" towards which Israel's and humanity's adventure leads.